Volatile fatty acids and microbial load of West African dwarf rams fed ammonium sulphate-fortified diets (2016)
Growing West African Dwarf (WAD) rams, aged between 6 and 8 months with mean body weight of 12.80 ± 0.12kg were used to predict rumen microbial population and volatile fatty acids (VFAs) for 105 days. The growing WAD rams were randomly allotted to four dietaiy treatments with four rams per treatment group in a completely randomized design. The compared experimental diets were: Each group was assigned to experimental diet shown below and ammonium sulphate at inclusion level of 0, 2.5, 5.0, 7.5g/kg (NH(4)2SO(4) were added to it as Tl, T2, T3 and T4 respectively. Results showed that, rumen ammonia nitrogen coneentration (1.17mg/100ml), rumen bacteria (7.17cfu/ml), rumen fungi (4.47 cfu/ml), rumen pH (6.82) and propionate acid (33.25mmol/100ml) were significantly (P < 0.05) highest in growing rams on T4 compared to other treatment diets. Rumen temperature (38.95°C), rumen protozoa (5.39ml), acetic acid (21.51%) and butyric acid (12.85%) were significantly (P < 0.05) better in growing WAD rams on Tl. Propionate formation can be considered as a competitive pathway for hydrogen use in the rumen and it ranges from 19.25-22.41 mmole/100ml and is statistically difference because sulphate reducing bacteria compete with methanogenic archaea for hydrogen when sulphate is present Also, ammonium sulphate can be referred to as anti-methanogenic compounds because it reduces the protozoal numbers in the rumen and it ranges from 5.36 to 5.95 mi. It was concluded that, ammonium sulphate fortified diets is a potential source of readily available nitrogen and sulphur which enhances the growth of microbial population due to their high solubility and ability to be rapidly degraded to NH(3) in die rumen thereby enhancing ruminant productivity especially when fed at 7.5g/kg (NH(4)2SO(4).